Protective and antifungal properties of Nanodisk‐Amphotericin B over commercially available Amphotericin B. Issue 1 (1st March 2017) - Cho, Do‐Yeon; Hoffman, Kyle J.; Gill, Gobind S.; Lim, Dong‐Jin; Skinner, Daniel; Mackey, Calvin; Rowe, Steven M.; Woodworth, Bradford A.
Abstract : Objective: Amphotericin B (AMB), a potent antifungal agent, has been employed as topical and systemic therapy for sinonasal fungal infections. A novel formulation of nanodisc (ND) containing super aggregated AMB (ND‐AMB) for the treatment of fungal infections has been recently developed to provide greater protection from AMB toxicity than current, clinically approved lipid‐based formulations. The objective of the current study was to evaluate the safety and potency of ND‐AMB for sinonasal delivery using an in vitro model. Methods: Human sinonasal tissue was harvested during endoscopic sinus surgery and grown at air–liquid interface until well‐differentiated. Cultures were exposed to ND‐AMB vs AMB and changes in K + permeability and resistance were measured and recorded via Ussing chamber assay. Ciliary beat frequency (CBF) was analyzed in parallel as well as cytotoxic assay. Potency was assessed using real‐time PCR measurement of the Aspergillus fumigatus 18S rRNA. Results: Ussing chamber studies revealed K + currents that increased rapidly within 30 s of adding AMB (10 μg/mL) to the apical side, indicating apical membranes had become permeable to K + ions. In contrast, negligible induction of K + current was obtained following addition of ND‐AMB [AMB = (107.7 ± 15.9) μA/cm 2 AMB vs ND‐AMB = (2.3 ± 0.7) μA/cm 2 ND‐AMB; P = 0.005]. ND‐AMB also protected nasal epithelial cells from cytotoxicity of AMB ( P < 0.05). There was no difference in ciliary beat frequency between the two groups ( P = 0.96). The expression of A. fumigatus 18S rRNA with exposure of lower dose of ND‐AMB was significantly lower compared to that with AMB ( P < 0.05). Conclusions: Data from the present study suggests ND‐AMB protects human nasal epithelia membranes from AMB toxicity by protecting against apical cell K + permeability while maintaining uncompromised antifungal property compared to AMB. ND‐AMB could provide a novel topical therapy for sinonasal fungal diseases.